POTENSI KIJING LOKAL (Pilsbryoconcha exilis) SEBAGAI BIOFILTER TERHADAP PENURUNAN KADAR SIANIDA (CN) - Surono, .; Nisvera, Mela; Rahayu, Sata Yoshida Srie (Ekologia: Jurnal Ilmiah Ilmu Dasar dan Lingkungan Hidup, 2023)
Local gravestone (Pilsbryconcha exilis) is an animal that lives in fresh waters such as rivers, lakes, and other waters. The survival of local mussels is very high so that in large quantities it can be used as a water purification process due to pollutants and heavy metal pollution. Cyanide is commonly used to extract gold ore, waste that is wasted in waterways contains a lot of CN compounds so that it can pollute the living things in it. The purpose of this study was to determine the potential of local gravestone (Pilsbryoconcha exilis) as a biofilter to decrease cyanide (CN) levels. This study consisted of three treatments and one control (without KCN) with one replication. The number of mussels in each treatment amounted to 10 tails with the concentration of cyanide used was 0.04; 0.07; and 0.1 ppm. The results of this study indicate that local gravestone can affect the decrease in cyanide levels in the experimental aquarium media. In the treatment with KCN concentration of 0.07 ppm there was a decrease in cyanide levels of 0.011 mg/L and the treatment with 0.1 ppm KCN concentration decreased cyanide levels of 0.025 mg/L. The survival rate of the mussel during the research process was 100%, because there were no local dead mussels found. The best daily growth rate was in treatment 3 with 0.1 ppm KCN concentration of 2.3%.